2013
DOI: 10.3390/diseases1010036
|View full text |Cite
|
Sign up to set email alerts
|

The Nervous System Cytoskeleton under Oxidative Stress

Abstract: Abstract:Oxidative stress is a key mechanism causing protein aggregation, cell death and neurodegeneration in the nervous system. The neuronal cytoskeleton, that is, microtubules, actin filaments and neurofilaments, plays a key role in defending the nervous system against oxidative stress-induced damage and is also a target for this damage itself. Microtubules appear particularly susceptible to damage, with oxidative stress downregulating key microtubule-associated proteins [MAPs] and affecting tubulin throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 85 publications
(84 reference statements)
0
10
0
Order By: Relevance
“…To the best of our knowledge, such an observation has not been reported before for LN. The cytoskeletal abnormalities recorded by CLEM tomography in two regions of a LN and two regions of another LN of a different brain donor using 2D CLEM support the idea that neurofilaments become disrupted, possibly through proximally experiencing an increase of oxidative stress 38,39 . The 3D STED data also showed that LN contain many mitochondria and lysosomes.…”
Section: Discussionmentioning
confidence: 57%
“…To the best of our knowledge, such an observation has not been reported before for LN. The cytoskeletal abnormalities recorded by CLEM tomography in two regions of a LN and two regions of another LN of a different brain donor using 2D CLEM support the idea that neurofilaments become disrupted, possibly through proximally experiencing an increase of oxidative stress 38,39 . The 3D STED data also showed that LN contain many mitochondria and lysosomes.…”
Section: Discussionmentioning
confidence: 57%
“…55 Oxidative stress is a key mechanism that causes aggregation of a number of proteins implicated in neurodegenerative disorders. 55,56 HQ induces F-actin aggregation through the phosphorylation of the P38/HSP27 cascade in ARPE-19 cells. 37 In the current study, we found that HQ also induced F-actin aggregation, P38 activation, and HSP27 phosphorylation in donor RPE cells, and RSG cotreatment abrogated these effects.…”
Section: Discussionmentioning
confidence: 99%
“…In the event of oxidative stress, NFs are phosphorylated, leading to the formation of protein aggregates. In AD brains, for example, there is an increased N-malondialdehydelysine formation which destroys NFL proteins [44] . Therefore, cerebellar degeneration associated with NaN 3 and AlCl 3 -induced AD involves the dysregulation of NFL and possibly other cytoskeletal proteins in the cerebellum of rats, because cytoskeletal components are interconnected through cross-linking proteins, and damage to one component affects the entire cytoskeletal network.…”
Section: Gbc Prevents Astrogliosis and Nf Pathology In Cerebellar Cortexmentioning
confidence: 99%